2016
DOI: 10.1016/j.survophthal.2015.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of visual quality after endothelial keratoplasty

Abstract: Endothelial keratoplasty is now favored over full-thickness penetrating keratoplasty for corneal decompensation secondary to endothelial dysfunction. Although endothelial keratoplasty has evolved as surgeons strive to improve outcomes, fewer patients than expected achieve best corrected visual acuity of 20/20 despite healthy grafts and no ocular comorbidities. Reasons for this remain unclear, with theories including anterior stromal changes, differences in graft thickness and regularity, induced high order abe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 142 publications
(226 reference statements)
1
35
1
1
Order By: Relevance
“…In a recent review, it was concluded that the limiting factor of vision after DSAEK remains unknown (Turnbull et al. ). Here, we used a prospective design and a repeated‐measures mixed model that incorporated data from all time‐points.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent review, it was concluded that the limiting factor of vision after DSAEK remains unknown (Turnbull et al. ). Here, we used a prospective design and a repeated‐measures mixed model that incorporated data from all time‐points.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review concluded that the reason for limited visual outcome after DSAEK remains uncertain (Turnbull et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…145 Despite all these advantages, the visual results in some patients may be less than optimal even with fully functional grafts with no ocular comorbidities, suggesting that there is a ceiling on what can be achieved in some cases. 134…”
Section: Treatments For Endothelial Diseasementioning
confidence: 99%
“…It is also possible that simple corneal endothelial stripping, if successful, could address some of the limiting factors in achieving the highest visual outcomes seen in EK surgery. 134 Reforming the endothelial barrier without the use of donor tissue could reduce the higher order aberrations and light scatter that are known to reduce visual acuity after DSAEK as well as remove any scatter caused by a donor-host interface. 107 On the other hand, the prolonged edema that persists until the endothelium closes could induce anterior corneal stromal changes that may be more detrimental to long-term visual acuity.…”
Section: Potential Advantages Of Simple Corneal Endothelial Strippingmentioning
confidence: 99%
“…In a recent review on the matter, it was concluded that the limiting factor of vision after DSAEK remains unknown (Turnbull et al. ).…”
Section: Introductionmentioning
confidence: 99%